Creative layers and continuities: A case study of Nicole Lizée and the Kronos Quartet - Bayley, Amanda; Lizée, Nicole (Musicae Scientiae, 2016)
This study examines the creative layers and continuities evident within the composition and rehearsal processes of Nicole Lizée’s Golden Age of the Radiophonic Workshop (Fibre-Optic Flowers), written for the Kronos Quartet in 2012. Lizée’s compositional approach to the historic and the new, and the mechanical and the human, are interpreted through Simon Emmerson’s three themes of combination, transformation, and control, and his three “impulses within composition” that combine live and acousmatic soundworlds – integration, antithesis, and co-existence. These concepts also help to articulate the way the players engage with the physical, psychological, and expressive demands of the piece. Discussions arising from the Kronos Quartet rehearsing the piece with the composer reveal how extensions are made to the performers’ mind and body experiences when they are required both to initiate and integrate sounds emanating from unfamiliar, analogue machines into their acoustic, yet amplified soundworld. Creative layers and continuities are seen to evolve from compositional experimentation and from composer–performer and co-performer dialogues in rehearsal in the BBC Maida Vale studio prior to the world premiere at a BBC Prom concert on 24 July 2012.
Publisher: SAGE Publications Ltd
Keywords: Delia Derbyshire; Kronos Quartet; Radiophonic Workshop; composition; creativity; electronic sounds; interaction; notation; rehearsal; string quartet

Layers of creativity in composition, rehearsal and performance: Nicole Lizée and the Kronos Quartet - Bayley, Amanda; Lizée, Nicole (2013)